Of Boyling and Seething: A Re-evaluation of the Common Cooking Terms in Connection with Brewing - Susan Verberg (EXARC, 2018)
Modern chemistry provides us with a deeper understanding of fermentation, but that does not necessarily translate into an easier interpretation of medieval recipes. Our modern brewing methods and sanitary measures have evolved, and the language and terminology used in brewing has changed over the years. (Anderson, 2005, pp.5-24) The arcane language of early medieval recipes often makes modern interpretations approximations at best, and modern brewers with their own interpretation of the same recipe make variations which sometimes differ slightly and sometimes substantially. This article takes an in-depth look at two 14th century English mead recipes and discusses alternate interpretations of specific cooking terminology as applied in medieval brewing.